Romania : Technical Assistance Report- Improving Compliance Risk Management of Large Taxpayers. (IMF Staff Country Reports; Country Report, 2016)
This Technical Assistance report discusses measures for improving compliance risk management of large taxpayers in Romania. The Large Taxpayer Office (LTO) Risk Management Unit needs appropriately skilled staff and good analytic facilities to identify and mitigate risks. The existing structure has too many people reporting directly to the LTO Director General. The changes in staff following restructuring will present an opportunity to renew and enhance LTO staff capabilities to better support modern risk-based methods. The risk decision making and transparency in the LTO also need to be improved to support compliance management.